A systematic review of dyadic studies examining relationship quality in couples facing colorectal cancer together. Issue 1 (26th January 2017) - Kayser, Karen; Acquati, Chiara; Reese, Jennifer Barsky; Mark, Kristen; Wittmann, Daniela; Karam, Eli
Abstract: Background: Despite the adverse effects that treatment for colorectal cancer can have on patients' quality of life and, in particular, their intimate relationships, very little research has been conducted on the psychosocial adjustment for both patients and their partners/spouses. Objectives: The aim of this systematic review was to examine dyadic studies of adjustment in couples in which one partner has been diagnosed with colorectal cancer. Methods: Pub Med, PsychINFO, MEDLINE, Social Sciences Abstracts (EBSCO), and the Cochrane Library were systematically searched for studies reporting quality of life outcomes for colorectal cancer patients and their partners/spouses. Only studies that included dyads in the sample were eligible for inclusion. The Quality Assessment Tool for Quantitative Studies was used to evaluate each study. Results: A total of 277 studies were identified, of which 9 studies met the inclusion criteria (N = 388 couples). The methodological quality of the studies was high in that they used standardized instruments validated with their samples, conducted dyadic data analyses (when appropriate), and used longitudinal designs. A synthesis of the studies revealed that (1) relationship factors (eg, support, communication, dyadic coping, and relationship satisfaction) affect adjustment to cancer; (2) cancer‐related distress impacts each partner's adjustment or the relationship; and (3) gender, role (patient/caregiver), and clinical characteristics (treatment, mental health) can mediate adjustment to cancer. Conclusion: The quality of the relationship can influence patients' and their partners' adjustment to colorectal cancer. Psychosocial interventions that address relationship issues may be beneficial to couples facing the challenges of colorectal cancer.